Typical applications and realization of SDN in IP WAN - Yongjun HUANG; Xiaoming LU; Weihua CAO (Dianxin kexue, 2016)
Three key points of SDN are decoupling of data plane and control plane，centralized control and open interfaces.Some carriers develop a SDN application system based on RR+ or PCE technology in order to achieve the centralized control function on traditional IP WAN.The architecture and development suggestions of the SDN application system were presented，and some typical functions，such as routing optimizing，traffic balanced scheduling，paths intelligent arrangement and so on，were described.